Bronchopulmonary Dysplasia: Crosstalk Between PPARγ, WNT/β-Catenin and TGF-β Pathways; The Potential Therapeutic Role of PPARγ Agonists - Lecarpentier, Yves; Gourrier, Elizabeth; Gobert, Vincent; Vallée, Alexandre (Frontiers in Pediatrics, 2019)
Bronchopulmonary dysplasia (BPD) is a serious pulmonary disease which occurs in preterm infants. Mortality remains high for lack of effective treatment despite significant progress in neonatal resuscitation. In BPD, the persistence of the canonical WNT / b-catenin pathway at a too high level at the canalicular stage disturbs the pulmonary maturation at the saccular and alveolar stages. The excessive alveolar wall thickness impairs a normal diffusion of oxygen and carbon dioxide responsible for hypoxia. Transforming growth factor (TGF-b up-regulates the canonical WNT signaling and inhibits the peroxysome proliferator activated receptor gamma (PPARg). This profile is observed in BPD, especially in animal models. At premature birth, hypoxia favors the canonical WNT / TGF-b axis at the expense of PPARg. This promotes the differentiation of fibroblasts into myofibroblasts, a prelude to pulmonary fibrosis that impairs the respiratory function after birth, during childhood and adulthood. Inhibiting the canonical WNT / TGF-b pathway could be a potential therapeutic target, as well as favoring the activation of PPARg, in particular by administration of nebulized PPARg agonists.